The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1515/forj-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Brilliant Blue dye solution with soil and its effect on mobility of compounds around the zones of preferenial flows at spruce stand

Abstract: We performed field experiment with 10 g l −1 concentration of Brilliant Blue solutes in 100 l of water sprinkling on 1 × 1 m surface of the Dystric Cambisol. Consequently, four vertical profiles were exposed at experimental plot after 2 hours (CUT 2), 24 hours (CUT 24), 27 hours (CUT 27) and after 504 hours (CUT 504) in order to analyse spatiotemporal interactions among the BB solution (Na-salts), soil exchangeable complex and fine earth soil (%) samples extracted from both the high and low coloured zones loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…It was found that the application of BB dye solution abruptly increased the pH (H 2 O) values in all profiles (CUT 2-CUT 504) of the experimental plot, and that the comparison with REF profiles revealed the gradual drop in pH (H 2 O) from CUT 2 to CUT 504 profiles. Bebej et al (2017) have documented also the changes of Na + concentration (cmol c kg −1 ) in the soil exchangeable complex extracted from the zones of macropore PF of CUT 2 -CUT 504 profiles, analogous with those described for pH (H 2 O).…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…It was found that the application of BB dye solution abruptly increased the pH (H 2 O) values in all profiles (CUT 2-CUT 504) of the experimental plot, and that the comparison with REF profiles revealed the gradual drop in pH (H 2 O) from CUT 2 to CUT 504 profiles. Bebej et al (2017) have documented also the changes of Na + concentration (cmol c kg −1 ) in the soil exchangeable complex extracted from the zones of macropore PF of CUT 2 -CUT 504 profiles, analogous with those described for pH (H 2 O).…”
Section: Discussionmentioning
confidence: 65%
“…objects (SPW < 20 mm) with small V v is located in this line, but high S V value is observed here (ten intercepts is visible in this line) Dye pattern profiles and corresponding dye pattern coverages (bottom) of CUT 2 (a), CUT 24 (b), CUT 27 (c) and CUT 504 (d) profiles (adapted fromBebej et al, 2017).…”
mentioning
confidence: 67%
See 3 more Smart Citations